Sintesis dan Karakterisasi Nanoenkapsulasi Sambiloto (Andrographis paniculata) Berbasis Karboksimetil Kitosan - Khulud Rihadatul 'Aisy; Sari Edi Cahyaningrum (Unesa Journal of Chemistry, 2024)
This study aims to synthesize and characterize the nanoencapsulation of sambiloto (Andrographis paniculata) extract based on carboxymethyl chitosan to improve the bioavailability of bioactive compounds. The sambiloto extract was obtained by maceration using methanol and subsequently encapsulated with carboxymethyl chitosan using ultrasonication method. Characterization results using a Particle Size Analyzer showed a particle size of 492.19 nm with a polydispersity index (PDI) of 0.3464, thus meeting the criteria for good nanoparticles in drug delivery systems. The pH stability test showed that the encapsulated sambiloto had relatively good stability. This suggests that carboxymethyl chitosan-based nanoencapsulation has the potential to protect bioactive compounds in the digestive system.